Rapid Weakening of Tropical Cyclones in Monsoon Gyres Over the Western North Pacific: A Revisit - Song, Kexin; Tao, Li; Gao, Jianyun (Frontiers in Earth Science, 2021)
The low-level monsoon trough over the western North Pacific (WNP) can evolve into a large cyclonic circulation, which is often termed a monsoon gyre (MG). Previous studies have revealed that tropical cyclones (TCs) embedded in MGs can experience rapid weakening (RW) and such RW might be attributed to the convective activity in the southeastern quadrant of the MG, which could induce asymmetries in a TC’s inner core structure, while the environmental factors, including the sea surface temperature (SST) and vertical wind shear (VWS), were not primary contributors to RW events. In this study, the possible role of large-scale environmental factors in association with the RW of TCs in MGs over the WNP is revisited based on the best-track TC and global reanalysis data during 2000–2018. Results indicate that TCs tend to weaken rapidly when they are embedded in the eastern semicircle of a MG, with the extreme RW events often occurring in the southeastern quadrant of a MG. However, different from previous studies, results from this study demonstrated that lower SST and strong large-scale VWS in the eastern semicircle of a MG are two major environmental factors contributing to the RW of TCs in MGs over the WNP. The different findings in this study from those in previous studies could be partly due to the different methods used to obtain the MG circulations and partly due to the environmental factors being analyzed in different quadrants of MG in this study.